Optimization of extraction parameters of total phenolic compound from Cosmos caudatus - Hazwani, Zulkiply (2012)
The wide ranges of extraction parameters used being identified from previous studies derives the need to find the best conditions to yield optimum extraction of total phenolic compounds from Cosmos caudatus. The objective of this research is to determine the optimum extraction parameters, namely ultrasonic frequency (from 30 to 70 kHz), sample-to-solvent ratio (from 2 to 10 w/v %) and extraction time (from 30 to 300 minutes) of total phenolic compound from Cosmos caudatus. The experimental design was first generated from Response Surface Methodology by using Design Expert 7.1.6 with three independent variables, namely ultrasonic frequency, sample-to-solvent ratio (SSR) and extraction time. Results showed that the optimization of extracting total phenolic compounds (TPC) from Cosmos caudatus can be accomplished by employing ultrasonic frequency of 70 kHz, 2g dry sample/100mL ethanol and extraction time of 300 minutes with yield of 7.7395 mg GAE/g dw which is in close agreement with the predicted value (7.5359 mg GAE/g dw). Analysis of variance showed significant ultrasonic frequency and sample-to-solvent ratio, but insignificant extraction time. This might be partly due to phenolic oxidation during the extraction itself. Since previous and present studies suggests that the extraction of total phenolic compounds can be further optimized, upcoming studies need to be directed at varying the significant extraction parameters including the extraction temperature, types of solvent used and extraction methods.